An Assessment to Measure Problem-Solving Ability and Science Process Skills: A Feasibility Test - Faila, Rohaya Evatri; Supahar, Supahar; Pebriana, Irvany Nurita (Universitas Muhammadiyah Makassar, 2025)
The ability to solve problems and apply scientific processes is a critical component of 21st-century education, especially within the context of the Indonesian